Bimetallic Ni–Cu alloy nanoparticles supported on silica for the water-gas shift reaction: activating surface hydroxyls via enhanced CO adsorption. Issue 10 (22nd December 2015) - Ang, M. L.; Miller, J. T.; Cui, Y.; Mo, L.; Kawi, S.
Abstract : Strong CO adsorption activates surface OH for enhanced WGS activity. Abstract : Highly dispersed Ni–Cu nanoparticles supported on SiO2 were synthesized via an in situ self-assembly core–shell precursor route. Monometallic (Ni and Cu) and bimetallic (Ni–Cu) catalysts were synthesized, characterized by XRD, H2 -TPR, XAS, XPS, CO-TPR, DRIFTS and N2 adsorption analysis and tested for the water-gas shift reaction. Formation of a highly dispersed Ni–Cu alloy was confirmed via XRD, H2 -TPR, XAS and DRIFTS. Oleic acid was found to promote the dispersion of both monometallic and bimetallic particles, anchoring small metal particles to the support via enhanced metal–support interactions. The DRIFTS results suggest that CO is adsorbed on the Cu sites in the Ni–Cu alloy thereby suppressing methanation. Additionally, stronger CO adsorption on the 5Ni5Cu/SiO2 (OA) catalyst activates the surface terminal hydroxyl groups on silica for enhanced CO conversion. The promotional effect of OA on the WGS activity was evidenced through kinetic measurements: the 5Ni5Cu/SiO2 (OA) catalyst obtained a turnover frequency of 0.004 s −1 which is twice that of the 5Ni5Cu/SiO2 catalyst (0.002 s −1 ).